The spatio-temporal characteristics of intercity green technology innovation transfer and its air pollution reduction effect in China - Guangzhi Qi; Zhibao Wang; Xumin Jiao; Chengxin Wang (Ecological Indicators, 2025)
Cross-regional green technology innovation transfer (GTIT) plays a vital role in mitigating climate change and improving environmental quality. However, its spatio-temporal dynamics and pollution reduction effects remain insufficiently understood. Using green patent transfer data during 2001–2021, this study examined intercity GTIT in China, identified transfer types, constructed a network structure, and explored its air pollution reduction mechanisms across regions and time periods. The results show a significant increase in green patent flows, with large regional disparities—transfers in the eastern region far exceed those in the central and western regions. A rhombus-shaped GTIT network has formed, centered on the Beijing-Tianjin-Hebei, Yangtze River Delta, Pearl River Delta, and Chengdu-Chongqing urban agglomerations, with Beijing emerging as the national hub. Moreover, intercity GTIT significantly reduces air pollution, with stronger pollution reduction effects observed in the eastern region compared to the central and western regions. The implementation of key policies in 2012 and 2017 further enhanced the pollution reduction effects. The pollution reduction effect also shows significant spatial spillover. Additionally, GTIT indirectly influences air pollution through industrial upgrading and the enhancement of local green innovation capabilities, which in turn promote cleaner production, lower energy consumption, and a shift toward more sustainable, low-emission industries. This study not only advances the understanding of GTIT in China but also offers insights and policy references for other countries aiming to harness green technology for sustainable development and environmental governance.